Safeguarding people with learning difficulties from forced marriage: the role of safeguarding adult boards - Clawson, Rachael (Emerald, 2016)
Purpose The issue of forced marriage is typically located within debates on violence against women, immigration control and cultural difference and is rarely considered in relation to adults with learning disabilities. The purpose of this paper is to argue that this is an issue which needs to be addressed by Safeguarding Adult Boards. Design/methodology/approach This paper draws upon original research undertaken by the author in conjunction with the Ann Craft Trust, a voluntary sector organisation which supports statutory, independent and voluntary sector organisations across the UK to protect adults at risk. The project sought to establish the extent to which the issue of forced marriage of people with learning disabilities is recognised, understood and acted upon by Boards. Findings Although many Boards are aware of national policy guidelines, very few had incorporated these guidelines into their local practice. There were two key consequences of this. First, Boards were failing to monitor cases of forced marriage and were unable to plan preventative services. Second, frontline workers were not given necessary training and so were unable to develop effective skills of knowledge. The need for both better recognition of and improved responses to the problem of forced marriage of people with learning disabilities is highlighted, as is the need for the safeguarding workforce to be supported by more effective strategic planning and better training. Originality/value This paper draws upon original research which examined how Safeguarding Adult Boards are responding to the issue of forced marriage of people with learning disabilities – a problem currently very much under-represented in existing research and practice literature.